Rancang Bangun Pembuatan Helm dengan Material Komposit Berbasis Serat Tebu dan Matriks Polyester - Hermawan, Dedy Andy; Wulandari, Diah; Sakti, Arya Mahendra; Riandadari, Dyah (Universitas Negeri Surabaya, 2024)
Along with the times, the helmet industry continues to innovate to develop lighter and stronger materials to improve performance and comfort for users. This study aims to find out the results of the analysis of the design of composite and polycarbonate helmets in impact testing on solidwork and to determine the results of compression testing of helmets using sugarcane fiber composite materials and polyester matrix. The experimental method used hand lay-up with a composition of 60% sugarcane fiber and 40% resin, a ratio of 10:1 between sugarcane fiber 1286 grams (length 15 cm), resin 105 grams, and catalyst 18.18 grams, as well as a variation in helmet thickness of 5 mm. The results of this research are a simulation of impact tests on helmets with composite materials with a load mass of 5 kg showing the highest impact deformation results of 6.551 x 10-02 mm, the highest impact equivalent strain of 9.197 x 10-05 MPa, and the highest impact von mises stress of 4.377 x 10+06 N/m2 and the results of the compression test with a helmet thickness of 5 mm, Fiber direction 0º, diameter 180 mm, and using ASTM D695 standard produces a maximum force of 0.86 kN, yield force 0.39 kN.